PENGARUH STORY TELLING TERHADAP TINGKAT KECEMASAN AKIBAT HOSPITALISASI PADA ANAK USIA PRASEKOLAH DI RSUD KOTA BEKASI 2013 - Irmawaty M.Kes, Lenny (Jurnal Kesehatan AYURVEDA, 2014)
ABSTRACTLenny IrmawatyHospitalization respond will increase the children anxiety level. Story telling is one of anxiety therapy which give hypnotic sensation and give a sugestion to child. Story telling make children become rilex and dissolved in story that given, and can decreased. Level of preschool childrenâs anxiety. The aim of this research is to knows the The effect ot story telling to level of childrenâs anxiety caused by hospitalization in pre schoolar children at RSUD Kota Bekasi 2013The method of this research was used quasi eksperiment with one group pretest-posttest design. The number of sampel are 39 respondens. The sample is pre schoolar children got hospitalization.Before story telling was alone means of anxiety level respondent was on moderate anxiety. After the story telling handle means of the anxiety level is on low anxiety. The result of statistic test shown p value 0.00<0.05 which means there is a significant effect The effect ot story telling to level of preschool childrenâs anxiety caused by hospitalization in pre schoolar children at RSUD Kota Bekasi 2013KeywordsÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  : Preschool Children, Anxiety, Story TellingReferencesÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  : 2006-2013Number of pageÂ Â Â Â Â Â Â Â Â  :58+xiv